Identification of faecal Escherichia coli isolates with similar patterns of virulence and antimicrobial resistance genes in dogs and their owners. Issue 1 (12th October 2022) - Naziri, Zahra; Derakhshandeh, Abdollah; Zare, Sahar; Akbarzadeh Niaki, Malihe; Motamedi Boroojeni, Azar; Eraghi, Vida; Shirmohamadi Sosfad, Abolfazl
Abstract: Background: The presence of antimicrobial resistance and virulence genes in Escherichia coli allows them to survive and cause infections. The close contact between humans and pets can reinforce the risk of transmitting resistant and virulent bacteria between them. Objectives: This study aims to compare the patterns of the presence of tetracycline and streptomycin resistance genes, as well as important virulence genes in E. coli isolated from faeces of healthy dogs and their owners. Methods: Polymerase chain reactions were performed for detection of antimicrobial resistance ( tetA, tetB, tetC, tetD, strA and strB ) and virulence ( fimH, iss, sitA and malX ) genes in 144 faecal E. coli isolates from 28 dog–owner pairs and 16 humans who did not keep any pets as controls. Results: Among the investigated antimicrobial resistance and virulence genes, tetA (52.1%) and fimH (86.8%) genes had the highest prevalence. No statistically significant difference was found between the prevalence of antimicrobial resistance and virulence genes in isolates of dogs and their owners. In total, 46.4% of dog–owner pairs had the same patterns of presence or absence of six antimicrobial resistance genes, 50.0% had the same patterns of presence or absence of four virulence genes and 25.0% had the same patterns of presence or absence of all 10 tested genes. Conclusion: The presence of antimicrobial‐resistant virulent E. coli in humans and pets may predispose them to infections that are hard to cure with conventional antibiotics. Notable frequency of dogs' and their owners' E. coli isolates with similar patterns of antimicrobial resistance and virulence genes may indicate the possibility of sharing virulent antimicrobial resistant E. coli between them. Abstract :